Cigarette smoke condensate induces centrosome clustering in normal lung epithelial cells. (9th January 2023) - Thaiparambil, Jose; Amara, Chandra S.; Sen, Subrata; Putluri, Nagireddy; El‐Zein, Randa
Abstract: Background: Unlike normal cells, cancer cells frequently have multiple centrosomes that can cluster to form bipolar mitotic spindles and allow for successful cell division. Inhibiting centrosome clustering, therefore, holds therapeutic promise to promote cancer cell‐specific cell death. Methods: We used confocal microscopy, real‐time PCR, siRNA knockdown, and western blot to analyze centrosome clustering and declustering using normal lung bronchial epithelial and nonsmall‐cell lung cancer (NSCLC) cell lines. Also, we used Ingenuity Pathway Analysis software to identify novel pathways associated with centrosome clustering. Results: In this study, we found that exposure to cigarette smoke condensate induces centrosome amplification and clustering in human lung epithelial cells. We observed a similar increase in centrosome amplification and clustering in unexposed NSCLC cell lines which may suggest a common underlying mechanism for lung carcinogenesis. We identified a cyclin D2‐mediated centrosome clustering pathway that involves a sonic hedgehog‐forkhead box protein M1 axis which is critical for mitosis. We also observed that cyclin D2 knockdown induced multipolar mitotic spindles that could eventually lead to cell death. Conclusions: Here we report a novel role of cyclin D2 in the regulation of centrosome clustering, which could allow the identification of tumors sensitive to cyclin D2 inhibitors. Our data reveal a pathway that can be targeted to inhibit centrosome clustering by interfering with the expression of cyclin D2‐associated genes. Abstract : We performed Real‐Time PCR, siRNA knockdown, western blot, and confocal microscopy to analyze centrosome clustering and declustering using normal lung bronchial epithelial cells exposed to CSC and compared to non‐small cell lung cancer (NSCLC) cell lines. We identified a cyclin D2‐mediated centrosome clustering pathway that involves SHH‐FOXM1‐CCND2‐CDK2 axis which is critical for mitosis plays a key role in CSC induced Beas‐2B cells. This study suggests a novel role for cyclin D2 in the regulation of centrosome clustering and reveal a pathway that can be targeted to inhibit centrosome clustering by interfering with cyclin D2 associated genes.